1997
DOI: 10.1093/oxfordjournals.jbchem.a021828
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Expression and Isoform Classification of a Minor Oleosin in Sesame Oil Bodies

Abstract: The oil bodies of plant seeds contain a triacylglycerol matrix surrounded by a monolayer of phospholipids embedded with alkaline proteins termed oleosins. Two distinct oleosins are present in the oil bodies of diverse angiosperms, and classified as high and low Mr isoforms according to their relative molecular masses in each species. In sesame oil bodies, besides the two ubiquitous oleosin isoforms (17 and 15 kDa), an additional minor oleosin (15.5 kDa) was revealed on Tricine SDS-PAGE. A full-length cDNA frag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 0 publications
2
20
0
1
Order By: Relevance
“…18) We set out to clone the other two sesame oleosin genes. With the sesame 15.5-kDa Holeosin probe, a full-length cDNA clone (accession no …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…18) We set out to clone the other two sesame oleosin genes. With the sesame 15.5-kDa Holeosin probe, a full-length cDNA clone (accession no …”
Section: Resultsmentioning
confidence: 99%
“…U43930) was 32 Plabeled and used as a probe to screen for sesame 17-or 15-kDa oleosin genes in the cDNA library as described elsewhere. 18) In the screening with the sesame 15.5-kDa oleosin probe, plaques with weak rather than strong signals were collected. We then excised the pBluescript phagemid from the Uni-ZAP XR vector in vivo from the plaques with weak signals on hybridization by the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Right after the kick-off studies on maize oleosins, homologous oleosin isoforms were subsequently identified in oil bodies of rapeseed (Brassica napus), soybean (Glycine max L.), carrot (Daucus carota), sunflower (Helianthus annuus), Arabidopsis thaliana, and cotton (Gossypium hirsutum) with their corresponding cDNA fragments cloned [27][28][29][30][31][32][33][34]. It seems that oleosin isoforms are universally present in oil bodies of angiosperm seeds including both monocotyledonous and dicotyledonous species [35][36][37][38][39]. Furthermore, oleosin isoforms found as the major proteins (approximately 80-90%) in seed oil bodies were demonstrated to shield the whole surface of the organelles in the company of phospholipids [40].…”
Section: Identification Of a Major Integral Protein In Seed Oilmentioning
confidence: 99%
“…Due to their secondary structure, oleosins form a meshwork-like organization on the lipid body surface. Oleosins are composed of two amphiphilic regions at the N and C termini, whereas the central part represents an expanded conserved domain composed of hydrophobic amino acids, which directly contacts the lipid matrix (30,78). The secondary structure of this hydrophobic domain was predicted to be an antiparallel ␤-strain in solvent (63), but more recent experiments performed on native oleosins suggest that it presents mostly as an ␣-helix (78).…”
Section: Nonprokaryotic Lipid Bodiesmentioning
confidence: 99%